Assessment of seven feed additives consisting of Lactiplantibacillus plantarum ATCC 55943, DSM 18112, DSM 18113, DSM 18114 and ATCC 55944, Lentilactobacillus buchneri ATCC PTA‐2494 and ATCC PTA‐6138, for all animal species (Pioneer Hi‐Bred International, Inc.) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal, 2025)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the assessment of the follow‐up applications for renewal of seven technological additives, Lactiplantibacillus plantarum ATCC 55943, L. plantarum DSM 18112, L. plantarum DSM 18113, L. plantarum DSM 18114, L. plantarum ATCC 55944, Lentilactobacillus buchneri ATCC PTA‐2494, L. buchneri ATCC PTA‐ 6138, as silage additives for all animal species. The additives are currently authorised. In the previous opinions, the FEEDAP Panel could not conclude on the full characterisation of the additives under assessment due to absence of data regarding the microbiological contamination and impurities. The applicant provided new data, which allowed the Panel to conclude on the characterisation of the products, and thereby its safety.